Association Between HLA-B*4001Genotype and Stavudine-induced Lipodystrophy in HIV patients: A Systematic Review and Meta-analysis - Tangamornsuksan, Wimonchat; Lohitnavy, Ornrat; Lohitnavy, Manupat (Asian Health, Science and Technology Reports, 2014)
Objectives: This study aimed to systematically review and quantitatively synthesize an association between HLA genotype and stavudine-induced lipodystrophy in HIV patients. Design: Systematic review and meta-analysis. Methods: A systematic search for studies that investigated the association between HLA genotype and stavudine-induced lipodystrophy was performed in six databases (i.e. PubMed, Embase, CINAHL, IPA, HuGENet, and Cochrane Library). A meta-analysis was conducted to determine the association between specific HLA genotypes and stavudine-induced lipodystrophy by using a random-effects model. Quality assessments were performed using Downs and Black checklist. Potential sources of heterogeneity were examined. Results: Two cross-sectional studies involving 439 HIV/AIDS patients who received stavudine-containing antiviral regimen (242 stavudine-induced lipodystrophy cases and 197 controls) were included. Only the prevalence of HLA-B*4001 genotype was investigated in both studies. We did not find any association between HLA-B*4001 and stavudine-induced lipodystrophy (overall OR = 3.13; 95% CI = 0.40-24.14) in a random-effects meta-analysis. A substantial heterogeneity was observed (I2 = 79.4%, p = 0.027). Conclusions: From our systematic review of a limited number of available studies, the association between HLA-B*4001 genotype and stavudine-induced lipodystrophy cannot be concluded. Ethnicity, duration of stavudine exposure, patient selection process and small sample size may contribute to the difference in results of the included studies. Future prospective studies with a larger sample size in Thai population and different ethnic groups are needed to verify the association between HLA-B*4001 genotype and stavudine-induced lipodystrophy.